2017
DOI: 10.1177/2325957417724207
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Feasibility of Smartphone Apps for HIV-Care Research with MSM and Transgender Individuals in Mpumalanga, South Africa

Abstract: There is an urgent need to develop the HIV treatment cascade for men who have sex with men (MSM) and transgender individuals in rural Mpumalanga, South Africa. Mhealth tools such as smartphone applications have the potential to support HIV self-care behaviors. We conducted an exploratory study with HIV-positive community leaders to understand their current uses of cell phones and smartphones and to assess their interest in an HIV research study that utilized a smartphone application for HIV care support. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Our use of HCD to guide our intervention adaptation process was efficient but dependent on the extensive preliminary research that was conducted prior (Daniels et al, 2018; Daniels, Lane, et al, 2017; Daniels, Struthers, et al, 2019). Such research facilitated identification of the intervention, HR, that aligned with GBMSM preferences for HIV treatment support and disclosure to partners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our use of HCD to guide our intervention adaptation process was efficient but dependent on the extensive preliminary research that was conducted prior (Daniels et al, 2018; Daniels, Lane, et al, 2017; Daniels, Struthers, et al, 2019). Such research facilitated identification of the intervention, HR, that aligned with GBMSM preferences for HIV treatment support and disclosure to partners.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of our participants had been living with HIV for at least 5 years, which may not represent all GBMSM like those newly diagnosed, interviews identified ongoing influences of HIV stigma on disclosure and relationships that are commonly shared. Second, our research has shown that GBMSM are willing to participate in video groups as a means of HIV intervention (Daniels, Lane, et al, 2017), and HR has been delivered in this mode effectively with a U.S. population (Marhefka et al, 2014; Turner et al, 2019). In this study, the positive feedback on such delivery showed that SOAR could be successful for GBMSM in South Africa.…”
Section: Strengths and Limitationsmentioning
confidence: 95%
“…Social media platforms and other information communication technologies should be used to encourage retention in HIV care services. 82…”
Section: Hivmentioning
confidence: 99%
“…GBMSM receptivity supports the group-based design of an intervention. Further, GBMSM are interested in HIV treatment interventions that use mobile health (mHealth) tools, and videoconference modalities offer the opportunity to create the group experience that GBMSM value [ 39 ]. Specifically, Daniels et al [ 39 ] showed that mHealth interventions are feasible, given that 71% of 20- to 25-year-old GBMSM own a smartphone.…”
Section: Introductionmentioning
confidence: 99%
“…Further, GBMSM are interested in HIV treatment interventions that use mobile health (mHealth) tools, and videoconference modalities offer the opportunity to create the group experience that GBMSM value [ 39 ]. Specifically, Daniels et al [ 39 ] showed that mHealth interventions are feasible, given that 71% of 20- to 25-year-old GBMSM own a smartphone. In the same study, 83% reported that they would be interested in engaging in a web-based platform for combined HIV and GBMSM support.…”
Section: Introductionmentioning
confidence: 99%